Faktor – Faktor yang Mempengaruhi Kejadian Pre-Hospital Delay pada Pasien Stroke - Syamsuddin, Fadli; Arsyad, Alyatul Islamiah; Harun, Karmila; Mohammad, Magfira; Damansyah, Haslinda; Ayuba, Asni; Yunus, Pipin; Sudirman, Andi Nur Aina; Ismulail, Andi Muh Rifqi (Jurnal Keperawatan Florence Nightingale, 2024)
Pre-hospital delay is a medical term that refers to the time spent from the onset of the first symptoms or signs of stroke until the patient arrives at a medical service or hospital for treatment. There are several factors that influence the delay in treatment (prehospital delay) for stroke, including age, gender, residence status. educational factors, economic level, distance from residence, time of stroke, type of transportation, and family response. The aim of this research is to determine the factors that influence pre-hospital delay in stroke patients. The research design uses quantitative correlational with cross sectional. Sampling used probability sampling with the allocation proportional cluster random sampling technique with a total of 78 respondents. Data were collected using observation and questionnaires. Chi square test apply and multivariate using multiple logistic regression test. The results showed that the variable factors were age (p. 0.466 > 0.05), gender (p. 0.972 > 0.05), residence status (p. 0.000 < 0.05), education level (p. 0.000 < 0.05), economic level (p . 0.002 < 0.05), distance of residence (p. 0.003 < 0.05), time of attack (p. 0.000 < 0.05), transportation obtained (p. 0.000 < 0.05) and family response variables (p. 0.000 < 0.05). Multivariate analysis showed that the family response was OR=15.026, followed by the education variable OR=8.335, and the time of stroke OR=8.143. The conclusion is that the family response has a 15 times chance or is the most dominant influence on pre-hospital delay in stroke patients at the Gorontalo Provincial Regional Hospital